Nonbanks, credit provision and the transmission of monetary policy in Denmark - Dominic Cucic; Denis Gorea (Danmarks Nationalbank, 2021)
We analyse the role of nonbank lenders in corporate and consumer credit markets in Denmark and show that they affect the transmission of monetary policy to financial and real outcomes. Nonbanks increase their share of credit supply after an interest rate hike in both the consumer and corporate credit markets.
Keywords: 330; Monetary policy; Lending rate; Financial sector